2020
DOI: 10.1080/14773996.2020.1787701
|View full text |Cite
|
Sign up to set email alerts
|

Safety risk factors in two different types of routine outsourced work: a systematic literature review

Abstract: Outsourcing generates risks for client firms but these vary according to the contracted task. This systematic literature review reports on 50 empirical studies that investigate the safety risk factors associated with outsourcing aligning them with the three categories of safety risk factors identified by Underhill and Quinlan in their PDR-Model. By using a 2x2 framework based on the strategic value of the task to the client firm (core or peripheral) and its level of complexity (complex or routine) we could com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Causal pathways and connections within and between the three dimensions are exemplified in Quinlan et al (2001) and later applications (Bohle et al, 2015, Underhill & Quinlan, 2011. While OHS risks have been indirectly referenced as being a function of legislative requirements (Pilbeam et al, 2020, Quinlan & Bohle, 2009, with Underhill and Quinlan (2011) suggesting this dimension to partly underlie the other two factors, the hierarchical structure of the model has not been explicitly elaborated on.…”
Section: Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Causal pathways and connections within and between the three dimensions are exemplified in Quinlan et al (2001) and later applications (Bohle et al, 2015, Underhill & Quinlan, 2011. While OHS risks have been indirectly referenced as being a function of legislative requirements (Pilbeam et al, 2020, Quinlan & Bohle, 2009, with Underhill and Quinlan (2011) suggesting this dimension to partly underlie the other two factors, the hierarchical structure of the model has not been explicitly elaborated on.…”
Section: Developmentmentioning
confidence: 99%
“…At a conceptual level, the model places precarious employment practices at the centre (or in the background) of all three dimensions at different levels of impact, showing their effect on workers but also how they challenge work organization, existing regulatory frameworks and stakeholders outside employment relationships (for example labour inspectorates or occupational health service providers). Applying the model in a literature review on OHS of outsourced work, Pilbeam et al (2020) found that the three dimensions were applicable to analyse both firm-individual as well as firm-firm relationships.…”
Section: Developmentmentioning
confidence: 99%
See 3 more Smart Citations